Dampak Regulasi POJK 51/2017 Terhadap Kualitas Pengungkapan GRI Pada Emiten Sektor Konstruksi - Ucok Jimmy; Agus Munandar (Journal of Business and Economics Research (JBE), 2026)
This study analyzes the impact of Financial Services Authority Regulation (POJK) Number 51/2017 concerning Sustainable Finance on the conformity of sustainability report disclosures of construction companies listed on the Indonesia Stock Exchange (IDX) with the 2021 GRI Standards. The research method uses a quantitative method on annual reports and sustainability reports from a sample of state-owned and private construction companies during the 2015–2023 period using a purposive sampling technique. Analysis indicators refer to the main framework of the GRI 2021 which includes economic, environmental, and social dimensions. The results show that POJK 51/2017 plays a significant role as a catalyst in increasing transparency and accountability in sustainability reporting, with a clear trend of increasing GRI indicator disclosures after 2017. However, a clear disparity was found in the depth and consistency of disclosures between state-owned construction companies and private construction companies. State-owned construction companies demonstrated higher levels of compliance and faster adaptation, with an average disclosure score of 58.9 points (46%), driven by strong institutional mandates and regulatory oversight from BP Danantara, BP BUMN, and the Financial Services Authority (OJK). Private construction companies, on the other hand, tended to adapt more slowly, with an average disclosure score of 30.6 points (24%), and their reporting remained primarily compliance-focused, requiring stronger market incentives and investor pressure to achieve full alignment with global standards. The findings of this study confirm the effectiveness of POJK 51/2017, which directs reporting to the 2021 GRI standards. However, internal capacity building, policy harmonization, and a more comprehensive integration of environmental, social, and governance indicators are needed to achieve holistic sustainability reporting in the Indonesian construction sector.